L'effet de différents facteurs géométriques sur l'écoulement du trafic routier - Application des modèles d'automates cellulaires - Nassab, Khalid (Université Hassan II - Mohammedia, Faculté des Sciences Ben M'Sik, Casablanca, 2004)
The congestions are the fundamental problems of the road traffic. They can be, particulary, due to the geometrical factors, wich can lead to the macroscopic effects even if they occupy only one minimal region of a road. The motorway junctions influence the road traffic flow. They reduce the capacity of the motorways. In particular, the effect of these junctions depends on ramps nature, wich constitute them (junctions), and on spacing between them (ramps). The motorways capacity reduced by the ramps effect can be increased using the overtaking process, if the motorways are with multiple lanes. The connection lanes in the motorway systems behave like opened systems, whose flows at the boundaries are ordrerd by the total number of the vehicles of the motorway system considered and by the rates of lane change in the regions of the on- and off-ramps, which constitutes these boundaries. In the case of the real traffic, these rates of the lane change are distributed on the sites of these ramps. The taking into account of these distributions in the simulation models can improve the motorways capacity. The maximum flow of the traffic in an open system depends on the procedure of the vehicles insertion to its left boundary. The application of an insertion similar to the process of the lane change in the regions of the ramps allows access to the states of the traffic flow, wich are accessible in the deterministic NaSch-model in the periodic systems. The flow entering through a on-ramp towards the main lane of a motorway becomes very limited at high densities and high fluctuations of vehicles speeds. To improve this flow, it is possible to take into account of the so-called ’’Reiverschluss’’ process in the simulation models. This process can be added to the rules of the lane change in the vicinities of the on-ramp. In the case of partial reductions of the motorways lanes, this process plays an important part in the regulation of the traffic before the beginning of the reduced lanes. In the simulation models of the road traffic, the application of this process requires changes in the rules of the lane change in the region of its application (application of the Reiverschluss process) and also in its neighbouring regions. In certain situations of the road traffic, empty spacings between the slow vehicles are not used by the fast vehicles. Consequently, these spacings can be seen as mobile reductions of the lanes. These spacing depends on the fluctuations of speeds of the last and slow vehicles and on the decisions of the drivers of the fast vehicles during an overtaking manoueuvre between two successive slow vehicles. Finally, the flucuations in 1/fα in the flow of the road traffic can be important in the representation of the simulation results of the road traffic like the distinction between the phases of the traffic flow and the behavior characterizing the phenomenon of inversion of the lane usage. The variations of the coefficient α which distinguish between the phases of the traffic flow are recognizable on the fundamental and phase diagrams.
Keywords: Ecoulement; Traffic routier; Facteur géométrique; Physique; Route; Modélisation des systèmes; Modèle d'automate cellulaire